A comparative study between Mannheims peritonitis index and Boeys score in predicting the morbidity and mortality in perforated pertic ulcer patients in a tertiary health care center in Bangalore - H. R., Harindranath; V. P., Mamatha (International Surgery Journal, 2022)
Background: Peptic ulceration is one of the major health problem encountered all around the world. Peptic ulcers are associated with complications like bleeding, perforation and obstruction with perforation being the most frequent complication. Objectives of current study were to compare the efficacy of MPI and Boey score in predicting the morbidity and mortality of patients with perforated peptic ulcer in a tertiary health care center in Bangalore which helps in stratification of the patients into different categories based on the likelihood of morbidity and mortality for more appropriate intensive care and management. Methods: A prospective observational study was conducted in a span of 9 months in the department of general surgery in Bangalore medical college and research institute. All the patients over 18 years with perforated peptic ulcer peritonitis who underwent laparotomy were included in the study. Data was appropriately tabulated; MPI and Boey score calculated and statistically analysed to predict morbidity and mortality of the patients. Results: Total number of subjects in this study was 75. Mean age was 44.53 years. Overall mortality was 32% (24 patients). Most common complication noted in this study was surgical site infection followed by pulmonary complications. Conclusions: Both MPI and Boey score were accurate in predicting the morbidity and mortality in PPU with higher scores having increased risk of morbidity and mortality. However, Boey score was more specific in predicting mortality and it can be used pre-operatively in predicting morbidity and mortality when compared to MPI which requires intra-operative findings for prediction.